Evaluating the value of collaboration systems in collocated teams: A longitudinal analysis - Saeed, Khawaja A. (Computers in Human Behavior, 2012)
Abstract: Distributed work structure has increased the importance of group work. Consequently, the usage of collaboration systems that support group work has increased exponentially. However, limited research exists on why collocated group members use collaborative system and how their perceptions about the system change from project initiation to project completion. The study proposes resource management support, coordination support, and evaluation support as key aspects based on which collocated users form beliefs about collaboration system value. Based on technology acceptance model and expectancy disconfirmation theory, we propose a model that examines the evolution of user beliefs from pre to post-adoption stage. Further, we argue that users may engage in different information processing strategies as part of the belief change process. The research model was examined based on longitudinal data collected from student groups working on a software application development project over a three month period. The results show that users deemed all features to be valuable at the pre-adoption stage. However, at the post-adoption stage evaluation support was the only factor that had a direct influence on collaboration system usefulness. While the impact of other support factors was mediated through the confirmation process. Further, users engaged in high information processing in revising their beliefs about collaboration system features, when they experienced a high level of dissonance. On the contrary, a dual information processing approach was visible in the context of support features that required adjustment or update to beliefs from pre to post-adoption stage. The study provides three core areas around which designers can structure collaboration system features to make it more useful. It also provides theoretical insights into the process through which user cognitions about collaboration system value change over time.